2019
DOI: 10.1093/mnras/stz581
|View full text |Cite
|
Sign up to set email alerts
|

Thick-disc model to explain the spectral state transition in NGC 247

Abstract: We propose the thick-disc model of Gu et al. (2016) to interpret the transition between soft ultraluminous state (SUL) and supersoft ultraluminous (SSUL) state in NGC 247. As accretion rate increases, the inner disc will puff up and act as shield to block the innermost X-ray emission regions and absorb both soft and hard X-ray photons. The absorbed X-ray emission will be re-radiated as a much softer blackbody X-ray spectrum. Hence NGC 247 shows flux dips in the hard X-ray band and transits from the SUL state t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
4
7
0
Order By: Relevance
“…A similar picture was proposed by Guo et al (2019) who argued that the ∼100s transitions can be explained by the viscous timescale with the X-ray flux variability driven by accretion rate fluctuations (atṁ 10). However, local fluctuations in theṀ might also cause variations in the winds, which could alter the source appearance (Feng et al 2016).…”
Section: Accretion Disc and Wind Physicssupporting
confidence: 73%
See 1 more Smart Citation
“…A similar picture was proposed by Guo et al (2019) who argued that the ∼100s transitions can be explained by the viscous timescale with the X-ray flux variability driven by accretion rate fluctuations (atṁ 10). However, local fluctuations in theṀ might also cause variations in the winds, which could alter the source appearance (Feng et al 2016).…”
Section: Accretion Disc and Wind Physicssupporting
confidence: 73%
“…The source is observed at a viewing angle that is high enough that the inner disc is already partly obscured by the wind (soft ULXs, left panel). An increase of the accretion rate pushes up the scale-height of the disc and the optically-thick base of the wind, causing an near-total obscuration of the inner regions and the source appears as an ultraluminous supersoft source (ULS, right panel, see also Pinto et al 2017, 2020b, Guo et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely due to strong reprocessing in an optically thick environment formed at R sph , where disc inflow is mainly inflated by internal radiation pressure. This picture is consistent with the observed low temperature, large radius, and super-Eddington luminosity (see Shen et al 2015;Soria & Kong 2016;Urquhart & Soria 2016;Guo et al 2019). The hotter component, which we fitted using a DISKBB, dominates the emission above 2 keV.…”
Section: Discussionsupporting
confidence: 88%
“…a change in the funnelling angle, where the region responsible for the harder emission become out of sight in SSUL state, which might also be linked to its compactness in the HID). Guo et al (2019) interpreted the SSUL/SUL transition according to the thick-disc model of Gu et al (2016), where the key physical parameter is the changing geometrical configuration of the system. This model also predicts the highest accretion rate in the SSUL regime where the inner regions are more obscured.…”
Section: The Normal Branch: From Ssul To Sulmentioning
confidence: 99%
“…Stobbart et al 2006;Urquhart & Soria 2016;Alston et al 2021) are not observed in the light curves of Holmberg II X-1 and NGC 5204 X-1, supporting this interpretation. It is thus likely that the dipping activity in ULSs is associated with direct obscuration of the inflated accretion disc as a result of the increased mass-accretion rate (Guo et al 2019). Hence, the increase in mass-accretion rate confers Holmberg II X-1 and NGC 5204 X-1 with a somewhat harder ULS aspect, because the SSUL aspect of these standard ULXs is not due to a high inclination angle, but rather due to the extreme narrowing of the funnel.…”
Section: Discussionmentioning
confidence: 99%